Making the Supply Chain visible Reporting of corporate social responsibility in the supply chain; An investigation into UK clothing retailers - Warren, Hayely Joanne (2010)
Purpose – This paper offers a preliminary exploration of the corporate social responsibility (CSR) issues being addressed by UK owned clothing retailers. The study focuses on what retailers disclose and report with regards to the social activities in their supply chain, and discusses whether the information provides a ‘visible’ account of the activities in the social supply chain.